Facial reconstruction following basal cell carcinoma: repair using a paramedian forehead flap-a case report - Juan, Orson R.; Baas, Manuel A.; Juan, Tomiko I.; Barrientos, Jonathan C.; Lozano, Jose L.; Villegas, Jesus E. C. (International Journal of Research in Medical Sciences, 2025)
Basal cell carcinoma (BCC) is the most common malignant cutaneous neoplasm, primarily affecting sun-exposed areas, with the nasal region being one of the most frequently involved sites. Here this report presents the case of a 68-year-old male presenting with an ulcerated lesion on the nasal tip, clinically consistent with nodular ulcerative BCC. A wide local excision was performed, and intraoperative frozen section analysis confirmed tumor-free margins. Reconstruction of the resulting full-thickness nasal defect was accomplished using a two-stage interpolated paramedian forehead flap. The postoperative course was uneventful, yielding an outcome that was both aesthetically satisfactory and functionally robust, with no evidence of recurrence during short-term follow-up. This case highlights the importance of meticulous oncologic resection and tailored reconstructive planning in managing complex nasal defects caused by skin cancer.